Question
upstudy study bank question image url

(c) Simplify the following: \( \begin{array}{lll}\text { (1) } \frac{3^{2 x+1}}{3^{2 x}} & \text { (2) } \frac{2^{x+5}}{2^{x+2}} & \text { (3) } \frac{5^{n+4}}{5^{m+5}} \\ \text { (4) } \frac{2^{3 x+5}}{2^{3 x+9}} & \text { (5) } \frac{6^{4 x-2}}{6^{4 x-4}} & \text { (6) } \frac{4^{n}}{2^{2 n-3}} \\ \text { (7) } \frac{7^{2 x-1}}{49^{x-1}} & \text { (8) } \frac{9^{x+1}}{3^{2 x} \cdot 81} & \text { (9) }-\frac{16^{p-3}}{8^{p-4}} \\ \text { (10) } \frac{5^{x} \cdot 25^{x-1}}{5 \cdot 125^{x}} & \text { (11) } \frac{9^{a} \cdot 4^{a-1}}{3^{2 a-1} \cdot 2^{2 a}} & \text { (12) } \frac{36^{x+2}}{6^{2 x+5}} \\ \text { (13) } \frac{50^{x+1}}{2^{x+1}} 25^{x+2} & \text { (14) } \frac{5 \cdot 45^{y}}{9^{y} \cdot 5^{y+2}} & \text { (15) } \frac{18^{x} \cdot 8^{x-1}}{9^{x+1} \cdot 4^{2 x-1}}\end{array} \)

Ask by Garrett Munoz. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the simplified results for each expression: 1. \( 3 \) 2. \( 8 \) 3. \( 5^{n-1-m} \) 4. \( \frac{1}{16} \) 5. \( 36 \) 6. \( 8 \) 7. \( 7 \) 8. \( \frac{1}{9} \) 9. \( -2^{p} \) 10. \( \frac{1}{125} \) 11. \( \frac{3}{4} \) 12. \( \frac{1}{6} \) 13. \( \frac{1}{25} \) 14. \( \frac{1}{5} \) 15. \( \frac{18^{x} \cdot 8^{x-1}}{9^{x+1} \cdot 4^{2x-1}} \)

Solution

Simplify the expression by following steps: - step0: Solution: \(\frac{7^{2x-1}}{49^{x-1}}\) - step1: Calculate: \(\frac{7^{2x-1}}{\left(7^{2}\right)^{x-1}}\) - step2: Calculate: \(\frac{7^{2x-1}}{7^{2x-2}}\) - step3: Calculate: \(7\) Calculate or simplify the expression \( \frac{9^{a} \cdot 4^{a-1}}{3^{2 a-1} \cdot 2^{2 a}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{9^{a}\times 4^{a-1}}{3^{2a-1}\times 2^{2a}}\) - step1: Factor the expression: \(\frac{3^{2a}\times 4^{a-1}}{3^{2a-1}\times 2^{2a}}\) - step2: Reduce the fraction: \(\frac{3\times 4^{a-1}}{2^{2a}}\) - step3: Factor the expression: \(\frac{3\times 2^{2a-2}}{2^{2a}}\) - step4: Reduce the fraction: \(\frac{3}{2^{2}}\) - step5: Evaluate the power: \(\frac{3}{4}\) Calculate or simplify the expression \( \frac{18^{x} \cdot 8^{x-1}}{9^{x+1} \cdot 4^{2 x-1}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{18^{x}\times 8^{x-1}}{9^{x+1}\times 4^{2x-1}}\) - step1: Factor the expression: \(\frac{9^{x}\times 2^{x}\times 8^{x-1}}{9^{x+1}\times 4^{2x-1}}\) - step2: Reduce the fraction: \(\frac{2^{x}\times 8^{x-1}}{9\times 4^{2x-1}}\) - step3: Factor the expression: \(\frac{2^{x}\times 8^{x-1}}{9\times 2^{4x-2}}\) - step4: Reduce the fraction: \(\frac{8^{x-1}}{9\times 2^{3x-2}}\) - step5: Factor the expression: \(\frac{2^{3x-3}}{9\times 2^{3x-2}}\) - step6: Reduce the fraction: \(\frac{1}{9\times 2}\) - step7: Calculate: \(\frac{1}{18}\) Calculate or simplify the expression \( \frac{5^{n+4}}{5^{m+5}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{5^{n+4}}{5^{m+5}}\) - step1: Multiply by \(a^{-n}:\) \(5^{n+4}\times 5^{-\left(m+5\right)}\) - step2: Calculate: \(5^{n+4}\times 5^{-m-5}\) - step3: Multiply: \(5^{n+4-m-5}\) - step4: Calculate: \(5^{n-1-m}\) Calculate or simplify the expression \( \frac{2^{x+5}}{2^{x+2}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{2^{x+5}}{2^{x+2}}\) - step1: Multiply by \(a^{-n}:\) \(2^{x+5}\times 2^{-\left(x+2\right)}\) - step2: Calculate: \(2^{x+5}\times 2^{-x-2}\) - step3: Multiply: \(2^{x+5-x-2}\) - step4: Calculate: \(2^{3}\) - step5: Evaluate the power: \(8\) Calculate or simplify the expression \( \frac{3^{2 x+1}}{3^{2 x}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{3^{2x+1}}{3^{2x}}\) - step1: Multiply by \(a^{-n}:\) \(3^{2x+1}\times 3^{-2x}\) - step2: Multiply: \(3^{2x+1-2x}\) - step3: Calculate: \(3\) Calculate or simplify the expression \( \frac{6^{4 x-2}}{6^{4 x-4}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{6^{4x-2}}{6^{4x-4}}\) - step1: Multiply by \(a^{-n}:\) \(6^{4x-2}\times 6^{-\left(4x-4\right)}\) - step2: Calculate: \(6^{4x-2}\times 6^{-4x+4}\) - step3: Multiply: \(6^{4x-2-4x+4}\) - step4: Calculate: \(6^{2}\) - step5: Evaluate the power: \(36\) Calculate or simplify the expression \( \frac{4^{n}}{2^{2 n-3}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{4^{n}}{2^{2n-3}}\) - step1: Calculate: \(\frac{\left(2^{2}\right)^{n}}{2^{2n-3}}\) - step2: Calculate: \(\frac{2^{2n}}{2^{2n-3}}\) - step3: Calculate: \(2^{3}\) Calculate or simplify the expression \( \frac{2^{3 x+5}}{2^{3 x+9}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{2^{3x+5}}{2^{3x+9}}\) - step1: Multiply by \(a^{-n}:\) \(2^{3x+5}\times 2^{-\left(3x+9\right)}\) - step2: Calculate: \(2^{3x+5}\times 2^{-3x-9}\) - step3: Multiply: \(2^{3x+5-3x-9}\) - step4: Calculate: \(2^{-4}\) - step5: Express with a positive exponent: \(\frac{1}{2^{4}}\) - step6: Evaluate the power: \(\frac{1}{16}\) Calculate or simplify the expression \( \frac{50^{x+1}}{2^{x+1} \cdot 25^{x+2}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{50^{x+1}}{2^{x+1}\times 25^{x+2}}\) - step1: Factor the expression: \(\frac{2^{x+1}\times 25^{x+1}}{2^{x+1}\times 25^{x+2}}\) - step2: Reduce the fraction: \(\frac{25^{x+1}}{25^{x+2}}\) - step3: Divide the numbers: \(\frac{1}{25^{x+2-\left(x+1\right)}}\) - step4: Subtract the terms: \(\frac{1}{25^{1}}\) - step5: Simplify: \(\frac{1}{25}\) Calculate or simplify the expression \( \frac{36^{x+2}}{6^{2 x+5}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{36^{x+2}}{6^{2x+5}}\) - step1: Calculate: \(\frac{\left(6^{2}\right)^{x+2}}{6^{2x+5}}\) - step2: Calculate: \(\frac{6^{2x+4}}{6^{2x+5}}\) - step3: Calculate: \(6^{-1}\) Calculate or simplify the expression \( -\frac{16^{p-3}}{8^{p-4}} \). Simplify the expression by following steps: - step0: Solution: \(-\frac{16^{p-3}}{8^{p-4}}\) - step1: Calculate: \(-2^{p}\) Calculate or simplify the expression \( \frac{9^{x+1}}{3^{2 x} \cdot 81} \). Simplify the expression by following steps: - step0: Solution: \(\frac{9^{x+1}}{3^{2x}\times 81}\) - step1: Multiply: \(\frac{9^{x+1}}{3^{2x+4}}\) - step2: Factor the expression: \(\frac{3^{2x+2}}{3^{2x+4}}\) - step3: Divide the numbers: \(\frac{1}{3^{2x+4-\left(2x+2\right)}}\) - step4: Subtract the terms: \(\frac{1}{3^{2}}\) - step5: Evaluate the power: \(\frac{1}{9}\) Calculate or simplify the expression \( \frac{5 \cdot 45^{y}}{9^{y} \cdot 5^{y+2}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{5\times 45^{y}}{9^{y}\times 5^{y+2}}\) - step1: Multiply by \(a^{-n}:\) \(\frac{5\times 45^{y}\times 5^{-\left(y+2\right)}}{9^{y}}\) - step2: Calculate: \(\frac{5\times 45^{y}\times 5^{-y-2}}{9^{y}}\) - step3: Multiply: \(\frac{5^{-1-y}\times 45^{y}}{9^{y}}\) - step4: Factor the expression: \(\frac{5^{-1-y}\times 9^{y}\times 5^{y}}{9^{y}}\) - step5: Reduce the fraction: \(5^{-1-y}\times 5^{y}\) - step6: Express with a positive exponent: \(\frac{1}{5^{1+y}}\times 5^{y}\) - step7: Rewrite the expression: \(\frac{5^{y}}{5^{1+y}}\) - step8: Calculate: \(5^{y-\left(1+y\right)}\) - step9: Calculate: \(5^{-1}\) - step10: Express with a positive exponent: \(\frac{1}{5}\) Calculate or simplify the expression \( \frac{5^{x} \cdot 25^{x-1}}{5 \cdot 125^{x}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{5^{x}\times 25^{x-1}}{5\times 125^{x}}\) - step1: Multiply by \(a^{-n}:\) \(\frac{5^{x}\times 25^{x-1}\times 5^{-1}}{125^{x}}\) - step2: Multiply: \(\frac{5^{3x-3}}{125^{x}}\) - step3: Factor the expression: \(\frac{5^{3x-3}}{5^{3x}}\) - step4: Divide the numbers: \(\frac{1}{5^{3x-\left(3x-3\right)}}\) - step5: Subtract the terms: \(\frac{1}{5^{3}}\) - step6: Evaluate the power: \(\frac{1}{125}\) Here are the simplified results for each expression: 1. \( \frac{3^{2x+1}}{3^{2x}} = 3^{(2x+1) - 2x} = 3^1 = 3 \) 2. \( \frac{2^{x+5}}{2^{x+2}} = 2^{(x+5) - (x+2)} = 2^{3} = 8 \) 3. \( \frac{5^{n+4}}{5^{m+5}} = 5^{(n+4) - (m+5)} = 5^{n-1-m} \) 4. \( \frac{2^{3x+5}}{2^{3x+9}} = 2^{(3x+5) - (3x+9)} = 2^{-4} = \frac{1}{16} \) 5. \( \frac{6^{4x-2}}{6^{4x-4}} = 6^{(4x-2) - (4x-4)} = 6^{2} = 36 \) 6. \( \frac{4^{n}}{2^{2n-3}} = \frac{(2^2)^{n}}{2^{2n-3}} = \frac{2^{2n}}{2^{2n-3}} = 2^{3} = 8 \) 7. \( \frac{7^{2x-1}}{49^{x-1}} = \frac{7^{2x-1}}{(7^2)^{x-1}} = \frac{7^{2x-1}}{7^{2(x-1)}} = 7^{(2x-1) - 2(x-1)} = 7^{2x-1-2x+2} = 7^{1} = 7 \) 8. \( \frac{9^{x+1}}{3^{2x} \cdot 81} = \frac{(3^2)^{x+1}}{3^{2x} \cdot 3^4} = \frac{3^{2(x+1)}}{3^{2x} \cdot 3^4} = \frac{3^{2x+2}}{3^{2x+4}} = 3^{(2x+2) - (2x+4)} = 3^{-2} = \frac{1}{9} \) 9. \( -\frac{16^{p-3}}{8^{p-4}} = -\frac{(2^4)^{p-3}}{(2^3)^{p-4}} = -\frac{2^{4(p-3)}}{2^{3(p-4)}} = -2^{4p-12 - 3p + 12} = -2^{p} \) 10. \( \frac{5^{x} \cdot 25^{x-1}}{5 \cdot 125^{x}} = \frac{5^{x} \cdot (5^2)^{x-1}}{5 \cdot (5^3)^{x}} = \frac{5^{x} \cdot 5^{2x-2}}{5^{1+3x}} = \frac{5^{x + 2x - 2}}{5^{3x + 1}} = \frac{5^{3x - 2}}{5^{3x + 1}} = 5^{(3x - 2) - (3x + 1)} = 5^{-3} = \frac{1}{125} \) 11. \( \frac{9^{a} \cdot 4^{a-1}}{3^{2a-1} \cdot 2^{2a}} = \frac{(3^2)^{a} \cdot (2^2)^{a-1}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a} \cdot 2^{2a-2}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a} \cdot 2^{2a-2}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a}}{3^{2a-1}} \cdot \frac{2^{2a-2}}{2^{2a}} = 3^{1} \cdot 2^{-2} = \frac{3}{4} \) 12. \( \frac{36^{x+2}}{6^{2x+5}} = \frac{(6^2)^{x+2}}{6^{2x+5}} = \frac{6^{2(x+2)}}{6^{2x+5}} = 6^{2x+4 - (2x+5)} = 6^{-1} = \frac{1}{6} \) 13. \( \frac{50^{x+1}}{2^{x+1} \cdot 25^{x+2}} = \frac{(2 \cdot 25)^{x+1}}{2^{x+1} \cdot (5^2)^{x+2}} = \frac{2^{x+1} \cdot 5^{2(x+1)}}{2^{x+1} \cdot 5^{2x+4}} = \frac{5^{2(x+1)}}{5^{2x+4}} = 5^{2x+2 - (2x+4)} = 5^{-2} = \frac{1}{25} \) 14. \( \frac{5 \cdot 45^{y}}{9^{y} \cdot 5^{y+2}} = \frac{5 \cdot (5 \cdot 9)^{y}}{9^{y} \cdot 5^{y+2}} = \frac{5^{1+y} \cdot 9^{y}}{9^{y} \cdot 5^{y+2}} = \frac{5^{1+y}}{5^{y+2}} = 5^{1+y - (y+2)} = 5^{-1} = \frac{1}{5} \) 15. \( \frac{18^{x} \cdot 8^{x-1}}{9^{x+1} \cdot 4^{2x-1}} = \frac{(2 \cdot 9)^{x} \cdot (2^3)^{x-1}}{(3^2)^{x+1} \cdot (2^2)^{2x-1}} = \frac

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To simplify these expressions, you'll mainly want to take advantage of the laws of exponents. Using the property \( \frac{a^m}{a^n} = a^{m-n} \) and the fact that other bases can often be expressed in terms of common bases will make this much simpler. 1. \( (1) \frac{3^{2x+1}}{3^{2x}} = 3^{(2x+1) - (2x)} = 3^1 = 3 \) 2. \( (2) \frac{2^{x+5}}{2^{x+2}} = 2^{(x+5)-(x+2)} = 2^3 = 8 \) 3. \( (3) \frac{5^{n+4}}{5^{m+5}} = 5^{(n+4)-(m+5)} = 5^{n-m-1} \) 4. \( (4) \frac{2^{3x+5}}{2^{3x+9}} = 2^{(3x+5)-(3x+9)} = 2^{-4} = \frac{1}{16} \) 5. \( (5) \frac{6^{4x-2}}{6^{4x-4}} = 6^{(4x-2)-(4x-4)} = 6^2 = 36 \) 6. \( (6) \frac{4^n}{2^{2n-3}} = \frac{(2^2)^n}{2^{2n-3}} = \frac{2^{2n}}{2^{2n-3}} = 2^{2n-(2n-3)} = 2^3 = 8 \) 7. \( (7) \frac{7^{2x-1}}{49^{x-1}} = \frac{7^{2x-1}}{7^{2(x-1)}} = 7^{2x-1-2x+2} = 7^{1} = 7 \) 8. \( (8) \frac{9^{x+1}}{3^{2x} \cdot 81} = \frac{9^{x+1}}{3^{2x} \cdot 3^4} = \frac{3^{2(x+1)}}{3^{2x+4}} = 3^{2x+2-2x-4} = 3^{-2} = \frac{1}{9} \) 9. \( (9) -\frac{16^{p-3}}{8^{p-4}} = -\frac{(2^4)^{p-3}}{(2^3)^{p-4}} = -\frac{2^{4(p-3)}}{2^{3(p-4)}} = -2^{4p-12-3p+12} = -2^{p} \) 10. \( (10) \frac{5^x \cdot 25^{x-1}}{5 \cdot 125^x} = \frac{5^x \cdot (5^2)^{x-1}}{5 \cdot (5^3)^{x}} = \frac{5^x \cdot 5^{2x-2}}{5^{1+3x}} = \frac{5^{3x-2}}{5^{3x+1}} = 5^{3x-2-3x-1} = 5^{-3} = \frac{1}{125} \) 11. \( (11) \frac{9^{a} \cdot 4^{a-1}}{3^{2a-1} \cdot 2^{2a}} = \frac{(3^2)^{a} \cdot (2^2)^{a-1}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a} \cdot 2^{2a-2}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a} \cdot 2^{2a-2}}{3^{2a-1} \cdot 2^{2a}} = 3^{1} \cdot 2^{-2} = \frac{3}{4} \) 12. \( (12) \frac{36^{x+2}}{6^{2x+5}} = \frac{(6^2)^{x+2}}{6^{2

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy